2019
DOI: 10.31742/ijgpb.79s.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Breeding rice for nitrogen use efficiency

Abstract: The aim of present investigation was to study the gross morphology and incidence of canine mammary tumors (CMTs) based on age, sex, breed, reproductive status and location along with histopathological classification and immunohistochemical characteristics. A total of 56 CMTs samples were collected from 49 cases of dogs. Gross morphology was studied in 26 cases of canine mammary tumors. For histopathological classification, samples were fixed in 10% formalin, embedded in paraffin and sections (5 μm thick) obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Increasing nitrogen use efficiency (NUE) is one important pathway to enhance sustainability, and several strategies and genetic approaches were described for NUE improvement [45][46][47]. Several efforts for NUE breeding in cereals and others field crops were published in rice [7,[48][49][50], wheat [51,52], maize [53][54][55][56], barley [57], millet [58], and oilseed rape [59]. In potato, breeding for NUE was also reported [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing nitrogen use efficiency (NUE) is one important pathway to enhance sustainability, and several strategies and genetic approaches were described for NUE improvement [45][46][47]. Several efforts for NUE breeding in cereals and others field crops were published in rice [7,[48][49][50], wheat [51,52], maize [53][54][55][56], barley [57], millet [58], and oilseed rape [59]. In potato, breeding for NUE was also reported [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…RDA with popular varieties (%) polished rice showed higher absorbed zinc through in vitro Caco-2 cell model and suckling rat pups studies (42). Preliminary studies of Indian Council of Medical Research-National Institute of Nutrition (ICMR-NIN) Hyderabad demonstrated that the zinc content and bioavailability from DRR Dhan 45 rice variety were almost twice those of the control IR64 (43). The clinical trial of one of the released biofortified rice varieties is under consideration by the Government of India.…”
Section: Gendermentioning
confidence: 97%
“…There are two major approaches to improving NUE, (1) conventional breeding techniques and (2) transgenic breeding approaches. There is strong evidence in rice, wheat, and canola to support conventional breeding methods for NUE improvement under various regimes of N availability (Kessel et al, 2012;Kowalski et al, 2016;Neeraja et al, 2019;Stahl et al, 2019). Similarly, overexpression and modification of genes through various transgenic approaches have led to NUE improvement in rice and wheat (Hu et al, 2018;Wang W. et al, 2018).…”
Section: Introductionmentioning
confidence: 99%